The role of the state in economic development - Guido Tabellini (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper discusses the recent literature on the role of the state in economic development. It concludes that government incentives to enact sound policies are key to economic success. It also discusses the evidence on what happens after episodes of economic and political liberalizations, asking whether political liberalizations strengthen government incentives to enact sound economic policies. The answer is mixed. Most episodes of economic liberalizations are indeed preceded by political liberalizations. But the countries that have done better are those that have managed to open up the economy first, and only later have liberalized their political system.
Keywords: O1; O11; 330; political liberalization; democracy; economic development; Entwicklung; Wirtschaftswachstum; Staatliche Einflußnahme; Institutionelle Infrastruktur; Entwicklungsländer